Polymer Solar Cells: Inter‐Fullerene Electronic Coupling Controls the Efficiency of Photoinduced Charge Generation in Organic Bulk Heterojunctions (Adv. Energy Mater. 24/2016). Issue 24 (December 2016) - Larson, Bryon W.; Reid, Obadiah G.; Coffey, David C.; Avdoshenko, Stanislav M.; Popov, Alexey A.; Boltalina, Olga V.; Strauss, Steven H.; Kopidakis, Nikos; Rumbles, Garry
Abstract : The generation efficiency of long‐lived photoinduced charges in polymer:fullerene bulk heterojunctions increases dramatically as the strength of intermolecular electronic coupling in the fullerene phase improves. Ultrafast geminate recombination is suppressed when electron delocalization within fullerene clusters is strong, while the opposite is observed when delocalization within the cluster is poor. In article number 1601427, Garry Rumbles and co‐workers show that the molecular design of the fullerene not only determines inter‐fullerene electronic coupling, but also influences the decay dynamics of free holes in the donor phase even when the polymer microstructure remains unchanged.